Occupational health surveillance of healthcare workers during COVID 19 pandemic: a narrative review: Occupational health surveillance during COVID-19 pandemic - d'Ettorre, Gabriele; Pellicani, Vincenza; Muratore, Massimo; Ceccarelli, Giancarlo (Acta Biomedica Atenei Parmensis, 2022)
Background and aims: Current literature has increasingly highlighted the risk of spreading the SARS-COV-2 infection in healthcare settings and showed the need for occupational health surveillance of HCWs during the current epidemiological emergency from COVID-19, as a preventive measure to minimize the spread of the infection. The purpose of this narrative review was to evaluate the literature and discover what the latest developments are about the management of the occupational health surveillance of healthcare workers (HCWs) during COVID-19 pandemic. Methods: We searched for publications in MEDLINE, Pubmed and Google Scholar using selected keywords. Each article was reviewed and categorized into one or more of the following three categories based on its subject matter: early diagnosis of COVID-19 in HCWs, detection of worker susceptibility to severe COVID-19, medical examination of HCWs returning to work after COVID-19. Results: Selected articles showed the RT-PCR test for Sars-CoV-2 as the gold standard to enable rapid identification of infected HCWs; an effective schedule of occupational health surveillance allows the identification of the susceptibility of the workers to severe Covid-19 and protect HCWs returning to work from the disease. Conclusions: The findings of the present narrative review show the need to strenghten the occupational health surveillance of HCWs during the current COVID-19 pandemic, with the aim not only to contain the spread of the infection in healthcare settings, but also to protect HCWs coming back to work after the disease.